Understanding the Mott insulating state in 1T-TaS2 and 1T-TaSe2 - Ying Fei; Zongxiu Wu; Wenhao Zhang; Yi Yin (AAPPS Bulletin, 2022)
Abstract In this article, we review the recent progress of the scanning tunneling microscopy studies of 1T-TaS2 and 1T-TaSe2 for bulk single crystals and molecular beam epitaxy monolayer films. We focus on how to understand the Mott insulating state in the whole set of materials, even when the stacking order takes effect. Based on this understanding, we discuss tuning the Mott insulator to a metallic state with different techniques, with Mott physics information revealed from the tuning process. The Kondo physics and quantum spin liquid state of 1T-TaS2 and 1T-TaSe2 are further discussed. This good platform of strong correlation must bring more intriguing phenomenon and physics in the future.